Dollar a day, 10 cents a dance - Dunn, Geoffrey; Schwartz, Mark. (New York Cinema Guild, 1984)
Presents a portrait of Filipino farm laborers who came to the U. S. in the 1920's and 1930's, expecting a more prosperous life-style. Voicing their recollections, these now elderly men reveal the poverty, and social and cultural difficulties they experienced.
Narrated by T. C. Colez.
Keywords: Filipino-Americans -- Social life and customs; Agricultural laborers, Foreign -- United States; Farm life -- History -- 20th century. -- United States